Potensi Zakat sebagai Filantropi Islam dalam Pemberdayaan Ekonomi - Lia Istifhamah (Jurnal Keislaman, 2020)
Abstract: Management of zakat which has been carried out by amil zakat as a whole has not been maximized so that the Islamic symbols have not been able to change the paradigm of society, especially Muslims. What needs to be done more intensely by BAZ / LAZ is the classification and grouping of the target recipients of zakat, namely the mustahiq groups that are suitable for receiving productive zakat and mustahiq which can only be given consumptive zakat (to meet daily needs). So that the implementation of Islamic da'wah through zakat as community economic empowerment can be optimal. The government must as soon as possible to revise the Law on Zakat which includes the procedures for managing Zakat, zakat regulation as a tax deduction, the formation of zakat departments / directorates in synergy with financial institutions / DG Tax. Keywords: Zakat, Islam, Economy